(untitled) (Islas, 2022)
ABSTRACT Introduction: The Association of Reporters of Havana (ARH) constitutes the first journalistic organization in Cuba, created on April 14, 1902. From 1941 to 1953, the lines of action were directed to the formation and development of journalists in the country. The organization of the First National Congress of Journalists, the promulgation of membership laws, the creation of the National Association of Journalists and the provincial branches, as well as the establishment of the «Manuel Márquez Sterling» Professional School of Journalism, were important steps beyond the framework of the capital, causing favorable impacts, not exempt from conflicts, in the professional and social recognition of journalists in Cuba. Methods: The theoretical methods such as the historical-logical, analysis-synthesis, inductivedeductive and the techniques of mixed or semi-standardized interview, allowed the study of the ARH, an important space for developing and channeling the demands of journalists, setting the foundations of a critical journalism and high professional rigor. Results: Taking into account the scarce research existing on the ARH during its vital existence (1902-1962) and the contributions to the journalistic guild, the training and professional development actions promoted by the Association, it is our aim to deepen from a historical perspective. The regional profile adopted clears up the relevance of the links that having its headquarters in the capital, impacted on professionals and apprentices all over the country. This research contributes to the studies of the history of press in Cuba, and enriches the sociohistorical studies about information and communication. Conclusions: From the Havana region, the ARH impacted on a much wider national profile, thus making possible to celebrate a First National Congress of Journalists, and the approval and implementation of the Journalistic Association process, as well as the creation of the «Manuel Márquez Sterling» Professional School of Journalism. These actions concretize the efforts of several decades to put an end to professional intrusion and to institutionalize the teaching of journalism in the country, characterized until then by empiricism